2023
DOI: 10.1088/1748-9326/acb835
|View full text |Cite
|
Sign up to set email alerts
|

4DEnVar-based inversion system for ammonia emission estimation in China through assimilating IASI ammonia retrievals

Abstract: Atmospheric ammonia has been hazardous to the environment and human health for decades. Current inventories are usually constructed in a bottom-up manner and subject to uncertainties and incapable of reproducing the spatiotemporal characteristics of ammonia emission. Satellite measurements, for example, Infrared Atmospheric Sounder Interferometer (IASI) and Cross-Track Infrared Sounder (CrIS), which provide global coverage of ammonia distribution, have gained popularity in ammonia emission estimation through d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In contrast, most other studies demonstrated a clearer seasonality in NH 3 emissions, with summer and winter seeing higher and lower emissions, respectively. ,,,,, Regarding nonagricultural sectors, in contrast to what the original EI could not adequately capture, isotopic results showed that the relative contributions of nonagricultural sectors also showed clear seasonal variations. , Consequently, the simulations driven by the MEIC would lead to a relative underestimation (overestimation) of NH 3 concentration during the summer (winter) season in this study. Zhang et al and Jin et al . also demonstrated that the MEIC underestimated and overestimated NH 3 emissions in the summer and winter seasons in the BTH region and China, respectively.…”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, most other studies demonstrated a clearer seasonality in NH 3 emissions, with summer and winter seeing higher and lower emissions, respectively. ,,,,, Regarding nonagricultural sectors, in contrast to what the original EI could not adequately capture, isotopic results showed that the relative contributions of nonagricultural sectors also showed clear seasonal variations. , Consequently, the simulations driven by the MEIC would lead to a relative underestimation (overestimation) of NH 3 concentration during the summer (winter) season in this study. Zhang et al and Jin et al . also demonstrated that the MEIC underestimated and overestimated NH 3 emissions in the summer and winter seasons in the BTH region and China, respectively.…”
Section: Results and Discussionmentioning
confidence: 93%
“…36,82 Consequently, the simulations driven by the MEIC would lead to a relative underestimation (overestimation) of NH 3 concentration during the summer (winter) season in this study. Zhang et al 83 and Jin et al 84 also demonstrated that the MEIC underestimated and overestimated NH 3 emissions in the summer and winter seasons in the BTH region and China, respectively. To characterize the NH 3 EI more accurately in the future, the monthly profile of NH 3 emissions in the MEIC must be significantly improved.…”
Section: Evaluation Of Isotope-corrected Nonagricultural Nh 3 Emissio...mentioning
confidence: 97%
“…These ground observations provide valuable insights on air pollution conditions and are widely used for model calibrations (Zhu et al, 2021), and their distributions are presented in Supplement Figure S3. Concurrently, the rapid advancements in satellite remote sensing and other technologies have made it possible to observe near-surface air pollutant abundances from space (Zhang et al, 2020;Jin et al, 2023a). For example, satellite onboard instruments such as the Ozone Monitoring Instrument (OMI) and the Tropospheric Monitoring Instrument (TROPOMI) can facilitate the measurement of nitrogen dioxide (NO 2 ) with extensive coverage (van Geffen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%